Structural and electrical characterization of a block copolymer-based unipolar nonvolatile memory device - Kang, Nam-Goo (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.